Determinants of household decision making autonomy among rural married women based on Ethiopian demography health survey: a multilevel analysis - Desalegn Anmut Bitew; Amare Belete Getahun; Getachew Muluye Gedef; Fantahun Andualem; Mihret Getnet (BMC Women's Health, 2024)
Abstract Introduction Decisions made at the household level have great impact on the welfare of the individual, the local community, as well as the welfare of the nation. Women’s independent decision on reproductive health increases women’s access to health information and utilization of reproductive services. This has great impact on maternal and child health outcomes. However, women in developing or low-income countries often have limited autonomy and control over their household decisions. Therefore the main purpose of this research project is to investigate the potential determinants of rural women’s household decision making autonomy. Methods A multi level analysis was performed using the fourth Ethiopian Demographic and Health Survey (EDHS) 2016 data set. A weighted sample of 8,565 married rural women was included in the final analysis. Women were considered to be autonomous if they made decisions alone or jointly with their husband in all three household decision components. It was dichotomized as yes = 1 and no = 0. Multico linearity and chi-square tests were checked and variables which did not fulfill the assumptions were excluded from the analysis. Four models were fitted. Variables with p-value ≤ 0.25 in the bi-variable multilevel logistic regression were included in the multivariable multilevel logistic regression. The Adjusted Odds Ratio (AOR) with a 95% confidence interval (95% CI) was computed. Variables with a P-value of less than 0.05 in the multi-variable multilevel logistic regression were declared as statistically significant predictors. Result A total of 8,565 weighted participants involved. From the total respondents, 68.55% (CI: 67.5%, 69.5%) of women had decision making autonomy. wealth index (poor: AOR: 0.84; 95% CI: 0.72, 0.97 and middle: AOR: 0.85; 95% CI 0.73, 0.98), literacy (illiterate: AOR: 0.75; 95% CI: 0.66, 0.86), respondents working status (Not working; AOR 0.68; 95% CI; 0.60, 0.76) ,who decides on marriage (parents: AOR 0.76; 95% CI; 0.67, 0.87), and proportion of early marriage in the community (high proportion of early marriage AOR: 1.35; 95% CI; 1.10, 1.72). Conclusion Women decision making autonomy was significantly determined by women economic participation (their wealth and their working status), women’s literacy, proportion of early marriage in the community and women’s involvement in decision of their marriage. Improving women’s economic participation and enhancing women’s participation to decide on their marriage will enhance women’s decision making autonomy.